2004
DOI: 10.1530/rep.1.00062
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II stimulates cAMP production and protein tyrosine phosphorylation in mouse spermatozoa

Abstract: Angiotensin II (AII), found in seminal plasma, has been shown to stimulate capacitation in uncapacitated mammalian spermatozoa. The present study investigated the location of AII receptors on spermatozoa and AII's mechanism of action. AT1 type receptors for AII are present on the acrosomal cap region and along the whole of the flagellum of both mouse and human spermatozoa. Because combinations of low concentrations of AII and either calcitonin or fertilization-promoting peptide (FPP), both known to regulate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 45 publications
0
27
0
1
Order By: Relevance
“…FPP, adenosine and calcitonin have been shown to regulate membrane-associated adenylyl cyclase (mAC)/cAMP, first stimulating cAMP production in uncapacitated cells and then inhibiting cAMP in capacitated cells . This made it plausible that AII was also affecting cAMP production and this has now been confirmed in a recent study (Mededovic & Fraser 2004) where AII was shown to stimulate cAMP in both uncapacitated and capacitated spermatozoa. In that same study, AT1 receptors for AII were found to be located in the acrosomal cap region and along the whole of the flagellum in both mouse and human spermatozoa, consistent with the enhanced fertility observed in AII-treated mouse sperm suspensions (Fraser et al 2001); successful fertilization requires changes in both the sperm head and flagellum.…”
Section: Introductionmentioning
confidence: 65%
See 3 more Smart Citations
“…FPP, adenosine and calcitonin have been shown to regulate membrane-associated adenylyl cyclase (mAC)/cAMP, first stimulating cAMP production in uncapacitated cells and then inhibiting cAMP in capacitated cells . This made it plausible that AII was also affecting cAMP production and this has now been confirmed in a recent study (Mededovic & Fraser 2004) where AII was shown to stimulate cAMP in both uncapacitated and capacitated spermatozoa. In that same study, AT1 receptors for AII were found to be located in the acrosomal cap region and along the whole of the flagellum in both mouse and human spermatozoa, consistent with the enhanced fertility observed in AII-treated mouse sperm suspensions (Fraser et al 2001); successful fertilization requires changes in both the sperm head and flagellum.…”
Section: Introductionmentioning
confidence: 65%
“…Although the study by Mededovic & Fraser (2004) confirmed that responses to AII involve a significant stimulation of cAMP production, it did not provide information on what elements might be involved in the signalling pathway. Current evidence suggests that the binding of FPP, calcitonin and adenosine to their respective receptors results in a G protein-mediated regulation of mAC, with the stimulatory responses involving Ga s and the inhibitory responses involving Ga i (possibly Ga i2 ); both Ga s and Ga i2 are found in the same regions as those receptors (Baxendale & Fraser 2003a).…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…report ( 8 ), Ang II also inhibits adenylyl cyclase/cAMP in rat heart myocytes, aorta and hepatocytes. On the other hand, Ang II stimulates cAMP production in some tissue ( 9 ), and may enhance cAMP production via Ca 2+ /calmodulin ( 10 ). An increase in adenylyl cyclase/cAMP by a rise in available Ca 2+ has also been suggested ( 11 ).…”
mentioning
confidence: 99%